PENGARUH TERAPI RELAKSASI OTOT PROGRESIF TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS CENDANA PUTIH II TAHUN 2017 - Lestari Lorna Lolo; Komang Ayu Rusmadewi (Voice of Midwifery, 2017)
High blood disease or hypertension is a condition which a person has increased systolic blood pressure more than 140 mmHg and diastolic blood pressure  more than 90 mmHg. Hypertension is a major risk the factor for ischemia and hemorrhagic stroke, myocardial infarction, heart failure, chronic kidney disease, cognitive decrease and premature death.The aim of this research is to analyze the effect of progressive muscle relaxation therapy for blood pressure decrease in hypertension patients in the work area of Cendana Putih II community health center 2017. This research is being quantitative, using quasi experimental (pretest-posttest design). The population in this research was hypertension patients in the work area of cendana putih II as many as 82 people with the number of samples 40 people with the method of sampling using purposive sampling. Data collected by questionnaire and analyzed univariat and bivariate using static test of Wilcoxon Signed Ranks Test.The conclusion of research proved that there was the effect of progressive muscle relaxation therapy for blood pressure decrease in hypertension patients with value P= 0,000 where value P < 0,05.The suggestion of this research will expected to be information to society, especially hypertension patients about progressive muscle relaxation therapy that can effect in blood pressure decrease. The information will hoped to help hypertension in stress management experienced, and give practical knowledge to do muscle relaxation therapy independently.Key Words : Muscle Relaxation Therapy, Blood Pressure, Hypertensio